Mind wandering, poor sleep, and negative affect: a threefold vicious cycle? - Fell, Juergen (Frontiers in Human Neuroscience, 2024)
Mind wandering (MW) is intricately linked to sleep and affect, bearing clinical relevance for various psychiatric conditions, notably attention deficit/hyperactivity disorder, depression, and anxiety disorders. Most reviews concur that the relationship between disturbed sleep and negative affect is bidirectional. The directional relationships between MW propensity and disturbed sleep, as well as MW propensity and negative affect, are less clear. Therefore, this brief review aims to examine the limited studies that have directly explored temporally sequential relationships. These studies provide clear evidence for an impact of affect on MW and of MW on sleep, along with less unequivocal evidence for an influence of MW on affect and sleep on MW. Collectively, these individual reinforcement loops may constitute a threefold vicious cycle, which may contribute to the development and perpetuation of psychiatric disorders. Available data convincingly suggest an impact cycle in the direction "MW propensity -> disturbed sleep -> negative affect -> MW propensity", while evidence for the inverse impact cycle is less pronounced.